Inherently safer process route ranking index (ISPRRI) for sustainable process design. (December 2022) - Athar, Muhammad; Shariff, Azmi Mohd; Buang, Azizul; Umer, Asim; Zaini, Dzulkarnain
Abstract: The growth of process industries has escalated the probability of loss containment scenarios of hazardous materials that can be tackled via process safety schemes. For preliminary design stage, the inherent scheme is more promising to generate sustainable process designs. For this purpose, various process routes are typically compared to recognize the safer one via numerous indexing methods to eliminate routes with hazardous materials. However, these indices lack in accommodating the equipment characteristics and the underutilization of process and chemical characteristics. Specifically for chemical characteristics, the toxicity aspect has not been engaged for process route selection in conjuction with other aspects. Consequently, an advanced indexing method is consolidated in the present work for the mentioned gaps named as inherently safer process route ranking index (ISPRRI). This method utilizes the equipment, chemical, and process aspects for ranking purposes. MMA process routes have been studied with the proposed method, and the obtained results validate the applicability to identify the less hazardous route and are in agreement with previous indices. The technique would facilitate the design engineers to rigorously compare the process routes to highlight the inherently safer route with less hazardous materials for the desired chemical product. Graphical abstract: Image 1 Highlights: Inherently safer process route ranking index (ISPRRI) is developed for process route selection. Equipment prospects cover type, size and ignition source. Temperature, pressure, viscosity and density define process aspects. Chemical aspects include toxicity, flammability and heating energy. MMA process is studied and results are compared with available indices.